A construção dos números reais desenvolvida por Richard Dedekind - Zanni, Rafaela Aparecida Camarinho (Universidade Federal de São Carlos, 2021)
In this work, we will study the emergence of incommensurability during classical antiquity and understand how this discovery was important for the development of real number theory during the arithmetic movement of analysis. Furthermore, our main focus will be on Richard Dedekind real number theory, studying and understanding the concept of “cuts” developed by him. Finally, we will briefly study, in a summarized way, the theory of Weierstrass and Cantor-Heine.
The construction of real numbers developed by Richard Dedekind
Keywords: Números Reais; Richard Dedekind; História da Matemática; CIENCIAS EXATAS E DA TERRA::MATEMATICA